Representative Speech in the "Genius Course" Video Collection on Fajrul FX's YouTube Channel - Della Rohmatul Husnah; Anggie Aurellia Majid; Najwa Firlia Salsabilla; Nailatun Rochmaniah Prameswari; Dita Aditya Prananda; Yetriana L. da Costa (Jurnal Sastra Indonesia, 2025)
In communicating and using language, humans perform a speech act. The speech act analyzed in this study is representative. This speech act informs and convinces the interlocutor of the truth of what is said. This study was conducted to analyze the forms of representative speech acts in nine videos in a playlist titled "Genius Course" on the YouTube channel Fajrul fx. A qualitative descriptive approach was used as the research methodology, and a pragmatic approach was used as the theoretical approach. The researcher used the note-taking technique, in which they first watched the selected videos and recorded the representative speech acts they contained. The data used in this study were from 9 videos in the playlist titled "Genius Course" on Fajrul FX's YouTube channel. The data analysis method used in this article was the distribution method, comprising several stages: listening, analyzing representative speech types, recording, grouping, and analyzing the speech context. The results of this study include 137 representative speech acts identified through the analysis. Among the nine analyzed videos, the speech act "showing" was the most frequently used, while "demanding" was the least. This research is expected to be a learning resource for the community, especially students and researchers. The researcher also hopes that future research on speech acts, especially representative speech acts, can address the shortcomings identified in this study.